Implementasi Disiplin Kerja dan Motivasi Kerja Pegawai pada Pusat Pengelolaan Pendapatan Daerah Wilayah Kabupaten Karawang - Siti Santi; Aji Tuhagana; Zenita Apriani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine and analyze work discipline and work motivation at the Regional Revenue Management Center of Karawang Regency. This research method uses qualitative methods with descriptive explanations. The data analysis techniques in this research are collecting information, reducing data, and drawing conclusions. The results of the research prove that there are still many employees who are still late when they are absent due to a lot of work, so those who are absent from going home through the application are forgotten and the application does not yet have a notification feature. Enforcing discipline is an effort to improve employee performance. Meanwhile, the motivation is quite good, given enthusiasm and always carried out evaluations every morning before starting work by the leadership, however there are still some employees who are still less motivated. However, according to Mr. Rian as the head of the center, every employee needs time to be motivated.